2017
DOI: 10.1016/j.jenvman.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically assisted photocatalysis: Highly efficient treatment using thermal titanium oxides doped and non-doped electrodes for water disinfection

Abstract: Electrochemically assisted photocatalysis (by electronic drainage) is a highly promising method for disinfection of water. In this research, the efficiency of photolytic oxidation using UV-A radiation and electrochemically assisted photocatalysis (with electric potential of 1.5 V) was studied by using electrodes prepared by thermal treatment and doped with silver, for inactivation of Escherichia coli and Staphylococcus aureus. The Chick-Watson microorganism inactivation model was applied and the electrical ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(78 reference statements)
0
9
0
2
Order By: Relevance
“…Some works have reported more efficient degradation of bacteria by PEC compared to UV or PC [ 47 , 130 , 131 ] under similar experimental conditions. The lab-scale experiments of Nie et al [ 132 ] showed that For E. coli K-12 all bacterial cells were completely killed by the PEC process within 180 s, whereas only ca.…”
Section: Combination With Other Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some works have reported more efficient degradation of bacteria by PEC compared to UV or PC [ 47 , 130 , 131 ] under similar experimental conditions. The lab-scale experiments of Nie et al [ 132 ] showed that For E. coli K-12 all bacterial cells were completely killed by the PEC process within 180 s, whereas only ca.…”
Section: Combination With Other Technologiesmentioning
confidence: 99%
“…The traditional apparatus consists of continuous-wave mercury lamps in low pressure (monochromatic at 253.7 nm) or medium pressure (polychromatic in the UV and visible light ranges) formats [ 46 ]. UV lamps that emit radiation at 254 nm (UV-C) are the ones with the highest germicidal effect [ 47 ].…”
Section: Photolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Uno de los procesos biológicos más populares son los procesos por lodos activos, mientras que, los procesos físicos comprenden a los de filtros empacados (arena, carbón activado); lamentablemente, la capacidad de remoción de los compuestos por estas metodologías es lograda solo parcialmente o, en ciertos casos el compuesto no sufre cambio alguno por lo que sólo es transportado de un medio a otro [1,3]. Entre los procesos químicos se ubican los AOPs, como procesos fotoquímicos, ya sean, ozonación, oxidación Fenton, tratamiento UV, electroquímica, entre otros [1,[4][5][6]. Estas tecnologías alternativas son eficientes en la degradación de compuestos orgánicos, debido a que muestran altos niveles de remoción y, sobre todo cuentan con una gran versatilidad en la desinfección de aguas por la generación de agentes con alto poder de oxidación.…”
Section: Introductionunclassified
“…4 , de las que se adicionaron 500 mL dentro del reactor. Una lámpara de mercurio Pen Ray de 254 nm (3300 −2 ) fue colocada de forma concéntrica dentro del reactor, manteniendo el sistema en agitación constante durante el proceso fotolítico.…”
unclassified